The application of computed tomography and magnetic resonance imaging at diagnostics of the human maxillofacial system; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Nikitin V.; Karavaeva E.; Cherepennikov Yu. M. Yuriy Mihaylovich; Miloichikova I. A. Irina Alekseevna (2016, 2016)
Title screen